Adolescents With Eating Disorders in Pediatric Practice – The European Academy of Paediatrics Recommendations - Rynkiewicz, Agnieszka; Dembiński, Łukasz; Koletzko, Berthold; Michaud, Pierre-André; Hadjipanayis, Adamos; Grossman, Zachi; Korslund, Kathryn; King, Bryan H.; Treasure, Janet; Peregud-Pogorzelski, Jarosław; del Torso, Stefano; Valiulis, Arunas; et al. (Frontiers in Pediatrics, 2022)
In the face of the growing number of adolescents suffering from eating disorders and access to psychiatric care limited by the epidemiological and demographic situation, the primary care pediatrician’s role in diagnosing and treating eating disorders is growing. The European Academy of Paediatrics (EAP) decided to summarize knowledge about eating disorders and formulate recommendations to support European pediatricians and improve care for adolescents with eating disorders.